2009
DOI: 10.1128/aac.01119-08
|View full text |Cite
|
Sign up to set email alerts
|

Bone Penetration of Amoxicillin and Clavulanic Acid Evaluated by Population Pharmacokinetics and Monte Carlo Simulation

Abstract: Amoxicillin (amoxicilline)-clavulanic acid has promising activity against pathogens that cause bone infections. We present the first evaluation of the bone penetration of a beta-lactam by population pharmacokinetics and pharmacodynamic profiling via Monte Carlo simulations. Twenty uninfected patients undergoing total hip replacement received a single intravenous infusion of 2,000 mg/200 mg amoxicillin-clavulanic acid before surgery. Blood and bone specimens were collected. Bone samples were pulverized under li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
(79 reference statements)
1
20
0
Order By: Relevance
“…Although CA itself has minimal antibacterial in vitro activity, when combined with beta-lactam antibiotics (amoxicillin) it enhances activity against non-ß-lactamase producing microorganisms and has a promising activity against pathogens that cause bone infections. 38 In the present study A-CA showed the lowest bacterial resistance; there was a significant statistical difference when compared with the clindamycin and amoxicillin groups. These findings are in agreement with reports from different countries, which suggest that A-CA is an excellent antibiotic alternative for primary and refractory dental infections, especially in acute endodontic abscesses/cellulitis.…”
Section: Discussionsupporting
confidence: 41%
“…Although CA itself has minimal antibacterial in vitro activity, when combined with beta-lactam antibiotics (amoxicillin) it enhances activity against non-ß-lactamase producing microorganisms and has a promising activity against pathogens that cause bone infections. 38 In the present study A-CA showed the lowest bacterial resistance; there was a significant statistical difference when compared with the clindamycin and amoxicillin groups. These findings are in agreement with reports from different countries, which suggest that A-CA is an excellent antibiotic alternative for primary and refractory dental infections, especially in acute endodontic abscesses/cellulitis.…”
Section: Discussionsupporting
confidence: 41%
“…Additional models were studied for which subcutaneous tissue and peritoneal fluid were described by additional compartments with a small volume of distribution (fixed to 0.1 liter), as we described previously (14). The small volume of distribution (0.1 liter) was chosen to not affect the overall PK behavior of meropenem.…”
Section: Methodsmentioning
confidence: 99%
“…An additive variability model was used for parameters estimated on log scale. A three-stage hierarchical analysis in S-ADAPT was performed to model the data of the time-kill experiments with various concentrations of Ca 2ϩ , Mg 2ϩ , or EDTA using methods described previously (37). The population PD results of the inoculum effect modeling in S-ADAPT were used as prior information.…”
mentioning
confidence: 99%